Pengembangan Kompetensi Sumber Daya Manusia melalui Pelatihan Manajemen Kinerja - Zulia Rifda Daulay; Khairatun Nazah; Nirwaty Tarigan; Tumini Sipayung; Ayu Wirda Ningsih (Ali Institute of Research and Publication, 2026)
This Community Service Activity (PKM) aims to improve human resource (HR) competencies through performance management training that focuses on understanding concepts, principles, and the application of effective and sustainable performance management systems. This activity was carried out among MSME groups affiliated with the Bumi Lestari Family Credit Union, Patumbak District, Deli Serdang Regency, which have been facing limitations in managing business performance and human resources. The implementation method used a participatory and applicative approach through lectures, discussions, simulations, and case studies. Evaluation was conducted through pre-tests and post-tests, as well as observations of the results of the participants' performance indicator development. The results of the activity showed an average increase in participants' understanding of 35%. In addition, participants were able to develop simple performance indicators relevant to the characteristics of MSMEs. This activity contributed to strengthening HR capacity and forming a performance-based work culture in partner MSMEs.